STAT4 gene polymorphisms in human diseases - Xia, Yan; Xie, Yanni; Zhang, Hao; Liu, Lunzhi (Frontiers in Immunology, 2024)
Signal transducer and activator of transcription 4 (STAT4) is a member of the STAT family, which is a group of transcription factors that regulate cytokine signaling.Genetic polymorphisms in STAT4 strongly influence immune responses and disease outcomes, especially in cancer and autoimmune diseases such as AIDs. Several studies have indicated that certain STAT4 gene variants are associated with alterations in STAT4 expression and/or activity and that there is a close relationship between STAT4 polymorphisms and drug efficacy. However, the underlying mechanisms are complex, and the roles of these polymorphisms in disease acquisition, progression, and severity are of widespread concern. Therefore, we provide an overview of the clinical significance of polymorphisms in STAT4 and the mechanisms by which these STAT4 variants are involved in various diseases.